Labour market turnover in Latin America: How intensive is it and to what extent does it differ across countries? - Beccaria, Luis Alberto (2020)
The study of labour market turnover is particularly significant in Latin America, which is characterized by marked economic cycles and limited social protection coverage. This article estimates the intensity of transitions from employment in six countries in Latin America in the new millennium and decomposes the differences observed, furthermore evaluating the employment destinations of workers making such transitions. The countries under analysis show very different turnover rates, which are mostly explained by a dissimilar incidence of informal and temporary employment. In all cases, a large share of job exits imply transitions to precarious jobs or unemployment.